The Management Of Flood Protection System Of Dewa Ruci Underpass In Bali - Risnadinata, Putu Martha; Kumara, I Nyoman Satya; Ariastina, Wayan Gede (Journal of Electrical, Electronics and Informatics; Vol 4 No 2 (2020): JEEI (August 2020)DO - 10.24843/JEEI.2020.v04.i02.p04, 2020)
Dewa Ruci intersection is one point of traffic congestion point in Bali. Dewa Ruci is a major intersection that connects the city of Denpasar, Kuta, Jimbaran, and Nusa Dua. In addressing traffic congestion, built underpass so that traffic becomes smooth when passing through the intersection Dewa Ruci. Part of the Dewa Ruci intersection is below the ground level, so risks of flooding. The source of water that potentially fills the underpass is groundwater seepage and rainfall. The flood protection of the underpass is capable of storing 1344 m 3 water and with the pumping system. In this research, the maintenance, operation, and management model of the flood protection system is developed that includes the development of organizational structures and standard operating procedures to ensure that the Dewa Ruci flood protection system works well sustainably.